Broad ion beam-scanning electron microscopy pore microstructure and multifractal characterization of shale oil reservoir: A case sample from Dongying Sag, Bohai Bay Basin, China. Issue 3 (May 2020) - Zhang, Pengfei; Lu, Shuangfang; Li, Junqian; Chang, Xiangchun; Li, Jijun; Li, Wenbiao; Chen, Guo; Wang, Siyuan; Feng, Wenjun
Pore structure and its heterogeneity are critical factors controlling the storage capacity and transportation properties of hydrocarbons. Broad ion-beam-milling scanning-electron microscopy allows for the study of a larger planar at high resolution than other methods and can provide insight into shale microstructures. In this study, we investigate the microscopic pore structure of a shale oil reservoir sample from Paleogene Shahejie Formation in Dongying Sag, Bohai Bay Basin, based on the broad ion-beam cross-section, and discuss the heterogeneity of the major pores using multifractal theory. The representative elementary area of the sample was first inferred to be ∼100 × 100 µm 2 (25 single images) for the broad ion-beam cross-section with an area of 1.054 × 0.915 mm 2 . Five pore types (interparticle, intraparticle clay, dissolution, inter-crystalline, and organic) were subsequently identified and analyzed in the selected typical representative elementary area. The results showed that interparticle, intraparticle clay, and dissolution pores were the major pore types and made a significant contribution to the total visible surface porosity (98.34%), whereas inter-crystalline and organic pores were not of great importance. Interparticle pores exhibited the most complex pore morphologies, the largest average pore diameter, and the simplest pore structure. Moreover, interparticle pores that were sub-parallel to the bedding plane showed the best connectivity. Intraparticle clay pores, on the other hand, had the smallest average pore diameter, the most complex pore structure, and their distribution in a two-dimensional plane was the most homogeneous. Dissolution pores were characterized by the least complex pore morphologies but more heterogeneous pore distribution. Both intraparticle clay and dissolution pores were abundant but possessed poor connectivity. We conclude that for shale oil storage and transportation in the Dongying Sag, interparticle pores play an important role in shale oil seepage, whereas intraparticle clay and dissolution pores provide the main space for the occurrence of shale oil.